Comparative Evaluation of Genetic Variability and Trait Associations for Fibre Yield and Quality Attributes in Two Cultivated Jute Species (Corchorus spp.) - Ray, Arghadeep; Dasgupta, Kumaresh; Hazari, Sourav; Kumari, Amrita; Mandal, G. S.; Roy, Anita (International Journal of Economic Plants, 2026)
The present investigation was conducted during the summer season of 2017–18 at the Teaching Farm, Bidhan Chandra Krishi Viswavidyalaya, Mondouri, West Bengal, to evaluate thirty jute genotypes (15 white and 15 tossa) for yield and fibre quality traits. Significant genetic variability was observed among the genotypes for all traits studied. Tossa jute generally exhibited higher values for plant height, green biomass, and fibre yield, while white jute showed superior fibre fineness. PCV values were slightly higher than GCV, indicating limited environmental influence. High heritability coupled with moderate to high genetic advance for all traits suggested the predominance of additive gene effects. Positive correlations were observed between fibre yield and traits such as plant height, green weight, fibre percentage, and basal diameter. Path coefficient analysis revealed that green biomass and fibre percentage had the highest direct contribution to fibre yield in both species. Genotypes JRC 517 and BCCO 6 were identified as promising for fibre strength, while CIN 94 and OIN 105 showed superior fibre fineness. These genotypes may serve as potential parents for the simultaneous improvement of yield and fibre quality in jute breeding programs.